ANALISIS KINERJA PROYEK “Y”MENGGUNAKAN METODE EARNED VALUE MANAGEMENT (Studi Kasus di PT Asian Sealand Engineering) - Elvi Wahyuni; Bambang Hendrawan (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2018)
PT Asia Sealand Engineering is a company engaged in offshore industry services. This study aims to profit. (EVM). The EVM concept of the three indicators is the Work Schedule Budget (BCWS), Work Performance Cost Budget (BCWP) and Actual Cost of Work Performance (ACWP). From these indicators are then analyzed to Cost Variance (CV), Cost Performance Index (CPI), Variance Schedule (SV) and Index Performance Schedule (SPI). After these talent indexes can be calculated Estimate at Completion (EAC), Estimate to Complete (ETC) and Time Estimate (TE). The project under study is project "Y" module 301 train 3, bacth 5 with job specification in Structure section. The results show that the project cost overrun and sechedule overrun. This means focusing the project down. Estimated cost of project lit (ETC) is Rp. 710.980.113.00. Total total cost can be seen from the calculation of EAC is Rp. 7.595.984.113, - and the estimated time to generate TE is 302 days.